The Politics of Postindustrial Social Policy: Family Policy Reforms in Britain, Germany, South Korea, and Sweden - Fleckenstein, Timo; Lee, Soohyun Christine (Comparative political studies, 2014)
Recent welfare reforms across the Organisation for Economic Co-operation and Development (OECD) have sought to make social policies more “employment friendly.” Although “old” social policies of the Golden Age (namely, unemployment protection and old-age security, which were typically geared toward the male breadwinner model) were subject to comprehensive retrenchment, “new” social policies, especially family policies facilitating work–family reconciliation and female employment participation, experienced substantial expansion. Following the Swedish “pioneer,” strong male breadwinner countries have expanded employment-oriented family policies since the late 1990s. Against the case of early family policy expansion in Sweden (typically associated with social democracy and an organized women’s movement), they examine whether the drivers of employment-oriented family policy have changed since the end of the Golden Age. The authors highlight party competition as key political driver in policy expansion in “latecomer” countries, whereas postindustrialization (in particular the rise of the new social risk of work–family conflicts, as well as wider changes in the skills profile and needs of postindustrial economies) provides the functional underpinnings for these policies.